Economic empowerment in South African agriculture - van Zyl, Johan; Kirsten, Johann F. (International Food Policy Research Institute, 1997)
One of the most important challenges facing the South African agriculture sector is the empowerment of previously disadvantaged people. The process of enabling black South Africans to become farmers in their own right will require some well-designed efforts to level the playing field and to bring about a more diverse agricultural society. This challenge requires a shift in agricultural policy. Although this policy shift implies a greater focus on the new client base, it would not necessarily mean that policy would discriminate against present commercial farmers. In fact, it would open a number of new opportunities for all farmers. In the end, these efforts could result in a more efficient agriculture sector that could provide the impetus for a growing rural economy.